PENGARUH FINANCIAL STABILITY, EXTERNAL PRESSURE, FINANCIAL TARGETS, INEFFECTIVE MONITORING, RATIONALIZATION PADA FINANCIAL STATEMENT FRAUD DENGAN PERSPEKTIF FRAUD TRIANGLE (Studi Empiris Pada Perusahaan Perbankan Periode 2012-2014 Yang Terdaftar Di Bursa - Selni Triponika Sari; Emrinaldi Nur DP; Rusli ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This research aims to obtain empirical evidence about effectiveness of the fraud triangle are pressure, opportunity and rationalization in detecting financial statement fraud. The variables of the fraud triangle that used is a pressure with proxy financial stability (ACHANGE), external pressure (LEVERAGE), and financial targets (ROA), opportunity with proxy ineffective monitoring (BDOUT), and rationalization with proxy rationalization (TATA). In this research to detecting financial statement fraud used a proxy earnings management with discretionary accruals as the dependen variabel. The population of this research is the banking companies listed in Indonesia stock exchange in 2012-2014. Total sample of this research is 35 banking companies with three years observation. Data analysis was performed with the classical assumption and hypotesis testing using linear regression. The result of this research indicates that the financial stability (ACHANGE), external pressure (LEVERAGE), rationalization (TATA) influence the financial statement fraud, meanwhile financial targets (ROA), ineffective monitoring (BDOUT) has no significan impact on financial statement fraud.Keywords : financial statement fraud, financial stability, external pressure, financial targets and ineffective monitoring